Biogenetic Paradoxes of the Nation : Finncattle, Apples, and Other Genetic-Resource Puzzles - Tamminen, Sakari (Book collections on Project MUSE., 2019)
"Biogenetic paradoxes of the nation is an ethnography of the patterns and paradoxes developing around the 1992 global Convention on Biological Diversity (CBD) treaty, which allowed the 196 signing countries to claim sovereignty over nonhuman life. Under this treaty, biodiversity is defined through the politics of nationhood and codified into commodifiable genetic resources. Focusing on the ethical dilemmas and legal aporias of this political and economic framework, Tamminen shows how the CBD's policies serve biodiversity conservation only in name, contributing more to the global neoliberal practice of ecological imperialism than to preservation. Through exploring how more-than-human worlds have formed an important part of the Finnish national imaginary prior to the signing of the CBD, and how the treaty has affected these relationships, Tamminen shows that in order to transform the "nation," we must change our understanding not only of what it means to be human, but also what it means to be in relationship with these more-than-human worlds"--Provided by publisher.